Kepribadian Tokoh Dalam Kumpulan Cerpen Menghardik Gerimis Karya Sapardi Djoko Damono: Kajian Psikoanalisis Sigmund Freud - Moch. Nur Riza Pratama Nugroho (Pusat Riset dan Inovasi Nasional, 2024)
Short stories are a form of literary work that reflects life in society with characters that dominate the storyline. The research is based on the researcher's interest in the personality of the characters in the story. The qualitative method in this study focuses on the narration, description, and interpretation of the character's personality in the short story collection